Effects of Seated Postural Sway on Visually Induced Motion Sickness: A Multiple Regression and RUSBoost Classification Approach - Park, Sangin; Mun, Sungchul (International journal of human-computer interaction, 2024)
The purpose of this study was to propose a model for estimating individual susceptibility to motion sickness by correlating measures of seated postural sway before exposure to a roller coaster movie displayed in a head-mounted display (HMD) with subjective ratings of visually induced motion sickness (VIMS). The participants were required to watch the content for 15 min, and seated center of pressure (sCOP) was measured using a force platform for 5 min before viewing. We developed a VIMS estimating model from 16 subjects and verified it on 15 subjects. SSQ scores for VIMS were strongly correlated with the area of sCOP, the main-to-minor ratio of the sCOP ellipse, and the total length of sCOP, respectively (r = 0.706, r = 0.555, and r = 0.622). When verifying the estimation model, the observed SSQ scores differed by 32.628 ± 29.749 from the expected SSQ scores, and both score sets were positively correlated (r = 0.622). The classification results between nil and mild, moderate, and severe groups for VIMS showed an accuracy of 0.74 using random under-sampling boost (RUSBoost).